The WBdigital Database: A Digital Repository for the Historical DIW-Wochenbericht, 1928–1968 - Marcus Schöps; Enrico Wedekind; Tobias Gebel; Andreas O. Kempf; Peter Löwe; Luca Kohlhepp; Alexander Gehrke; Frank Puppe (Jahrbücher für Nationalökonomie und Statistik, 2024)
Economic and social scientists are increasingly interested in historical data, but many relevant sources are still available in analog form, limiting accessibility and research potential. This article introduces the WBdigital database, which aims to improve this situation. The database provides digital access to the DIW Wochenbericht (1928–1968), including its economic texts and time series data covering both German and international perspectives. These research data offer an ideal framework for investigating important research questions related to historical contexts and current economic challenges. Thus, we hope that the WBdigital database will be a valuable tool for researchers interested in economic history.
Keywords: N01; N14; 330; economic history; interwar period; postwar period; database; Germany